Prevalence of Post-Traumatic Stress Disorder (PTSD) following COVID-19 Epidemic in Health Workers of Shahroud University of Medical Sciences - Hossein Ebrahimi; Seyedmohammad Mirhosseini; Mohammd Hasan Basirinezhad; Esmail Shariati (Hamadan University of Medical Sciences, 2021)
Background and Objective: Due to the growing prevalence of COVID-19 in the world and the increasing workload of health care providers, health workers face many problems such as long working hours, being away from family, and worrying about themselves and their families, which can affect their health and consequently challenge their job performance. The aim of this study was to investigate the prevalence of Post-Traumatic Stress Disorder (PTSD) following the COVID-19 epidemic in health workers of Shahroud University of Medical Sciences, Iran. Material and Methods: In this descriptive cross-sectional study, 228 Shahroud University of Medical Sciences health workers were studied from July 22 to August 22, 2020. Participants included nursing, medical, radiology, and laboratory personnel. The Demographic Information Questionnaire and PTSD Checklist - Civilian version (PCL-C) was completed online. Descriptive statistics and the multivariate linear regression model were used to analyze the data. Results: Based on the results, 85.5% of people were experienced PTSD. The regression determination coefficient (R2) was 15.1, so that men experienced 4.88 units of lower posttraumatic stress than women. People whose relatives died of COVID-19 experienced 7/04 unit higher PTSD than others. Conclusion: Given that a significant proportion of health workers experienced PTSD, senior treatment center managers must include more supportive measures to reduce PTSD in their work schedule.